Bibliotekos ir pasaulinė knygos produkcija - Vladimirovas, Levas (Knygotyra, 2026)
In the recent development of book editing and librarianship of the world we observe many striking paradoxical disproportions. On the one hand we are speaking about explosion of information and book production, on the other About book hunger characteristic not only for developing countries but sometimes for developed ones too where we still may discover regions of "cultural wastelands".To a great extent national book production and national library services are interdependent. But this correlation between the growth of book production and the growth of library holdings may remain only a mere postulate if not supported by appropriate coordinated actions of the government. The best example of a discoordination of both processes is the state of affairs which we find in this field in the United States – one of the biggest book producers of the world – with striking disproportions in the distribution of library book resources throughout the country. On the ground of statistical materials (UNESCO yearbook and others) the author of this paper proves that a correlation between the book production and the library holdings is practically feasible only in socialist countries with their planned economy. The main objective in determining an optimal ratio between these processes is to find the best solution in satisfying the cultural needs of the population.